Voice-Rate: A Dialog System for Consumer Ratings - Zweig, Geoffrey; Ju, Y. C.; Nguyen, Patrick; Yu, Dong; Wang, Ye-Yi; Acero, Alex (NAACL/HLT (Demonstration Program), 2007)
Voice-Rate is an automated dialog system which provides access to over one million ratings of products and businesses. By calling a toll-free number, consumers can access ratings for products, national businesses such as airlines, and local businesses such as restaurants. Voice-Rate also has a facility for recording and analyzing ratings that are given over the phone. The service has been primed with ratings taken from a variety of web sources, and we are augmenting these with user ratings. Voice-Rate can be accessed by dialing 1-877-456-DATA.